MANAJEMEN PENINGKATAN MUTU PENDIDIKAN DI MADRASAH ALIYAH NEGERI O2 LEBONG, BENGKULU - Erdiyanto Erdiyanto; Lukman Asha; Idi Warsah; Hamengkubuwono Hamengkubuwono (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
This study aimed to find a depiction of the steps taken by State Madrasah Aliyah 02 of Lebong Regency, Bengkulu, in improving the quality of education. This study used a qualitative approach because it was in accordance with the objectives having been formulated. The informants of this study were the principal, teachers, and school supervisors. Data were collected through three approaches, namely observation, interview and documentation. After the data were collected, then an analysis was carried out to obtain the following conclusion: improving the quality of education in MAN 02 Lebong Regency, Bengkulu, departed from the formulation of the Madrasah vision as the initial foundation of clear and measurable vision and missions with efforts to improve the quality of education well and achieve the objectives of madrasah education in the form of implementation in accordance with the characteristics, potential, and needs of students with superior quality education services through networking and school sisters with good quality schools.Keywords: Quality Of Education, Manadrasah management